PENERAPAN MANAJEMEN PEMASARAN DIGITAL UNTUK MENINGKATKAN DAYA SAING STARTUP DI PRODI MPI UIN SULTAN MAULANA HASANUDDIN BANTEN - Suryapermana, Nana (Yayasan Education and Social Center, 2024)
This research aims to fill this gap by exploring the factors that influence the application of digital marketing management in increasing the competitiveness of startups in the academic environment, as well as identifying existing challenges and opportunities. Using a qualitative approach and case study design, this research collected data through in-depth interviews, direct observation, and documentation studies from startup managers, entrepreneurship lecturers, and external stakeholders. The research results show that the digital marketing strategies implemented by MPI startups, such as the use of social media, digital content, and consumer data analysis, play an important role in increasing their competitiveness in a competitive market. However, challenges such as limited human resources and funds are the main obstacles in implementing digital marketing strategies. However, startup managers were able to overcome these obstacles with creativity and innovation. This research concludes that digital marketing provides a great opportunity for startups to strengthen their competitive position and support their growth. Implementing the right digital marketing strategy will contribute to the long-term success of startups in the digital era.